METHODOLOGICAL RECOMMENDATIONS: BLENDED LEARNING FOR FOREIGN LANGUAGE TEACHING IN PROFESSIONAL DEVELOPMENT FOR HEI PEDAGOGICAL STAFF - Giyasova Umida Erkinovna (Bright Mind Publishing, 2025)
This article addresses the organization of foreign language instruction within professional development courses through the implementation of a blended learning model. The concept of “blended learning” is defined based on an analysis of scholarly research in the field. A comprehensive overview of information and communication technologies (ICT) used in blended learning is provided, focusing on their didactic properties and functions that enhance the effective and purposeful execution of educational tasks. The article outlines an algorithm for developing a blended learning model for foreign language instruction and identifies the key principles for structuring educational content, along with methodological guidelines for organizing the learning process in a blended format.
Keywords: Blended learning, professional development, Higher Education Institution, information and communication technology, supportive blended learning model, blended learning substitution model, model of an e-learning consulting centre, multimedia, Learning Management System.